TINGKAT PEMAHAMAN GURU TERHADAP PENDEKATAN SAINTIFIK DAN IMBASNYA DALAM PENERAPAN PEMBELAJARAN DI MADRASAH TSANAWIYAH - MULIA RASYIDI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2019)
The implementation of the 2013 Curriculum in Indonesia defines several cores, namely the application of an integrated thematic learning process, using a scientific approach in learning, and authentic assessment. Some of the results of previous research on the application of the 2013 Curriculum, among others, were found that teachers who are less able to utilize resources to learn from the natural surroundings and teachers tend to maintain conventional teaching habits. From that, through this research, the researcher wants to describe how the teacher’s understanding of the scientific approach; how teachers make plans for implementing learning; how the teacher applies an approach that uses science in learning, and is there a contribution between understanding the scientific approach to the application of the learning process carried out by the teacher. The research method used is the Mixed Method Research model "Embedded Design". The results of this study can be concluded, namely: (1) In general, the teacher has understood the scientific approach, but has not understood how to implement this approach in learning in; (2) the lesson plan (RPP) made by the teacher has not been described in the implementation of learning activities oriented to a scientific approach; (3) The implementation of the learning carried out by the teacher does not reflect the application of the scientific approach; (4) Understanding the scientific approach contributes 13% to the implementation of learning. Therefore, to be able to apply a scientific approach is not only determined by understanding, but the teacher’s efforts are needed to always seek other knowledge that can increase and increase self-efficacy.